Capacity building, human capital investment and well- being among alumni of business apprenticeship training centers in Kaduna State, Nigeria - Yakubu, Haliru Idris (2017)
BATCs is an empowerment and poverty alleviation scheme aimed at enhancing and sustaining the wellbeing of its alumni in Kaduna state, Nigeria. It is an initiative aimed at assisting community development. Through participation in this scheme it is expected community member’s well-being is enhanced. Previously, there is no attempt to study the relationship between individual capacity building, human capital investment, economic empowerment and wellbeing. Hence, a gap exist for not addressing the levels and individual capacity building, human capital investment and dimensions of wellbeing which the researcher observed as limitations in this aspect. Based on the gap, this study emphasized on individual capacity building, human capital investment and wellbeing and examining the relationships between individual capacity building as well as human capital investment and dimensions of wellbeing among the BATCs alumni in Kaduna. This study also determine the mediating effect of economic empowerment on the relationship between capacity building, human capital investment and wellbeing. The study is quantitative in nature with a total of 267 respondents among BATCs alumni. The respondents were selected using the multistage cluster sampling technique from nine local government areas (LGAs) in Kaduna, Nigeria. They were surveyed using a structured questionnaire adopted and modified from previous literatures and administered by the researcher and trained enumerators. SPSS was used in analyzing the collected data thereby making meaning out of it from the descriptive analysis and also inferential analysis while the effect of individual capacity building, human capital investment to dimensions of wellbeing were determined using the Pearson product moment correlation analysis. Analyzed result shown that, there is high level individual capacity building, human capital investment and wellbeing among alumni of BATCs in Kaduna. Relatedly, the simple multiple regression of the Pearson correlation analysis indicates that the coefficient correlation were consistent with the hypothesis by indicating the significant contribution of individual capacity building, and human capital investment to dimensions of wellbeing. There is a mediating effect of economic empowerment indicated by the Sobel mediation test between the relationship of individual capacity building, human capital investment and wellbeing. The theories related to capacity building, human capital investment and wellbeing is supported by this study. The findings and recommendations of this study can be adopted and implemented by the Kaduna state government, other state governments, organizations and NGOs intending to establish or strengthen similar existing schemes as a policy framework towards enhancing their plan of action.